2023
DOI: 10.1021/acssuschemeng.2c06620
|View full text |Cite
|
Sign up to set email alerts
|

Ni@TiO2 Nanoarray with the Schottky Junction for the Highly Selective Electrochemical Reduction of Nitrite to Ammonia

Abstract: Electrocatalytic reduction of nitrite (NO 2 − ) is of vital significance for the removal of NO 2 − pollution and simultaneously making value-added ammonia (NH 3 ). Herein, Ni nanoparticles anchored on the TiO 2 nanoribbon array with the Schottky junction were successfully constructed for highly selective NO 2 − reduction to NH 3 . Density functional theory reveals the construction of the Ni@TiO 2 Schottky junction leads to charge rearrangement and optimized adsorptive energy of intermediates, assuring the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Therefore, it is necessary to develop an active, selective, and robust electrocatalyst that can efficiently convert nitrate to ammonia. With conventional metal-based catalysts, a respectable nitrate-to-ammonia selectivity can be achieved at low overpotentials and low current densities, whereas hydrogen evolution still dominates at high overpotentials. , Cu- and Ru-based electrocatalysts have received much attention for electrochemical ammonia synthesis from NO 3 – reduction because of their high electrochemical activity, customizable electronic structure, and affordable price. ,, Wang et al reported the incorporation of Cu into organic 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) for the highly selective reduction of NO 3 – to NH 3 with 85.9% faradaic efficiency . In order to efficiently convert NO 3 – to NH 3 , Wang et al developed an excellent Fe single atom electrocatalyst with an FE of 75% .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop an active, selective, and robust electrocatalyst that can efficiently convert nitrate to ammonia. With conventional metal-based catalysts, a respectable nitrate-to-ammonia selectivity can be achieved at low overpotentials and low current densities, whereas hydrogen evolution still dominates at high overpotentials. , Cu- and Ru-based electrocatalysts have received much attention for electrochemical ammonia synthesis from NO 3 – reduction because of their high electrochemical activity, customizable electronic structure, and affordable price. ,, Wang et al reported the incorporation of Cu into organic 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) for the highly selective reduction of NO 3 – to NH 3 with 85.9% faradaic efficiency . In order to efficiently convert NO 3 – to NH 3 , Wang et al developed an excellent Fe single atom electrocatalyst with an FE of 75% .…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have thus been made to develop non-precious metal-based alternatives. 6,7,[14][15][16][17][18][19][20][21] Ni has emerged as an interesting transition metal toward electrocatalytic NO 2 À RR and several Ni-based such catalysts are available, including vacancy-rich Ni, 22 CuNi alloy, 23 Ni@TiO 2 nanoarray 24 and Ni-carbon nanohybrid, 25,26 etc. Threedimensional (3D) Ni foam constructed by the dynamic hydrogen bubble template (DHBT) method possesses an interconnected open porous structure that can effectively prevent selfagglomeration of Ni during the reaction, eliminating the need for additional carriers and facilitating ion/electron transport for applications.…”
mentioning
confidence: 99%
“…1d) reveals distinct lattice fringes with a spacing of 0.204 nm, corresponding to the (111) plane of Ni. 26 24,25 The electrocatalytic performance of Ni foam/TP towards NO 2 À RR was investigated in an argon-saturated 0.1 M phosphate-buffered saline (PBS) solution, with and without the presence of 0.1 M NO 2 À , using a classical H-type cell equipped with three electrodes. Various colorimetric methods were employed to quantify the products of NO 2 À RR, including NH 3 and N 2 H 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Vulcan-supported NiFe layered double hydroxide (NiFe LDH/Vulcan) achieves an NH 3 production rate of 351 μmol h –1 mg –1 and a corresponding FE of 85%. Ji et al developed a titanium-plate-supported TiO 2 nanoribbon array decorated with Ni nanoparticles (Ni@TiO 2 /TP) for efficient ammonia synthesis via NO 2 RR . The obtained material features a Schottky junction, which is capable of regulating the electronic structure of the Ni sites and reducing the energy barrier of the RDS (Figure f,g).…”
mentioning
confidence: 99%